2016
DOI: 10.1093/ejcts/ezw147
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity in ventricular assist device patients: clinical relevance of pump speed and power

Abstract: Although VAD speed increase provided an additional pump flow of 1.6 l/min at peak exercise, no significant objective and subjective benefits on patients' exercise performance were observed. Finally, VAD power could be a useful parameter to monitor patients during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…C. AV open at peak exercise (Response type 1 with AV open): This category will include the most patients and benefits with speed increase will most probably result in outcomes similar to previous studies [23][24][25][26][27]36].…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…C. AV open at peak exercise (Response type 1 with AV open): This category will include the most patients and benefits with speed increase will most probably result in outcomes similar to previous studies [23][24][25][26][27]36].…”
Section: Plos Onementioning
confidence: 97%
“…The parameter Q MEAN is calculated over the whole cardiac cycle and therefore an indicator for overall hemodynamic changes rather than particular cardiovascular impairments. Generally, due to the instantaneous increase in preload with dynamic exercises a sudden increase of Q MEAN can be observed [4,32,[34][35][36]. However Q MEAN can increase to a different extent according to the residual ventricular contractility, LVAD speed setting as well as other parameters.…”
Section: Plos One Plos Onementioning
confidence: 99%
“…Dependencies between low LVAD speed (below baseline value) and reduced exercise capacities were found in the previous clinical studies . However, other studies investigating the effects of an LVAD speed increase under exertion, reported moderate to no improvements in terms of exercise capacity or TCO . Given the large patient diversity in terms of cardiovascular impairments, the benefits of an increased LVAD speed during exercise are still unclear.…”
Section: Introductionmentioning
confidence: 82%
“…3,4,9 Noor et al 6 observed that patients with a residual LV contractility are able to better accommodate an increase in TCO, resulting in higher exercise capacities. Fresiello et al 8 reported that LVAD power increased less at peak exertion in patients with better exercise capacity, indicating a possible increase in TCO mostly at the expenses of the LV. In addition, Gross et al 3 reported the importance of the cardiac response during exercise by observing correlations of peak oxygen consumption with HR and AV status, whereas Q LVAD showed no correlation.…”
Section: Evolution Of Tco In Different Exercise Profilesmentioning
confidence: 99%
See 1 more Smart Citation